Fatal Necrotizing Fasciitis following Episiotomy - Faris Almarzouqi; Gerrit Grieb; Christian Klink; Dirk Bauerschlag; Paul C. Fuchs; Ziyad Alharbi; Marketa Vasku; Norbert Pallua (Case Reports in Surgery)
Introduction. Necrotizing fasciitis is an uncommon condition in general practice but one that provokes serious morbidity. It is characterized by widespread fascial necrosis with relative sparing of skin and underlying muscle. Herein, we report a fatal case of necrotizing fasciitis in a young healthy woman after episiotomy. Case Report. A 17-year-old primigravida underwent a vaginal delivery with mediolateral episiotomy. Necrotizing fasciitis was diagnosed on the 5th postpartum day, when the patient was referred to our tertiary care medical center. Surgical debridement was initiated together with antibiotics and followed by hyperbaric oxygen therapy. The patient died due to septic shock after 16 hours from the referral. Conclusion. Delay of diagnosis and consequently the surgical debridement were most likely the reasons for maternal death. In puerperal period, a physician must consider necrotizing fasciitis as a possible diagnosis in any local sings of infection especially when accompanied by fever and/or tenderness. Early diagnosis is the key for low mortality and morbidity.